PRECARIOUSNESS OF FREELANCE JOURNALIST DURING COVID-19 PANDEMIC IN INDONESIA - Rana Akbari Fitriawan; Budi Irawanto; Oki Rahadianto Sutopo (Ravine Publisher, 2023)
Freelance journalists in Indonesia have a higher level of precariousness in terms of occupational health and safety, as well as socioeconomic conditions during the COVID-19 (Coronavirus Disease, 2019) pandemic. The vulnerability of exposure to the virus is caused by non-fulfillment of work equipment standards, health protocols when interacting with news sources, and inadequate health facilities. Another issue threatening freelance journalists is the deterioration of global economic conditions during the pandemic, which has had a devastating impact on corporate revenues. As a result, freelance journalists are also threatened with dismissal from work, late payment of wages, or even not paid at all. Referring to the concept of labor precariat from Guy Standing, this study aims to determine the factors that contribute to the vulnerability of freelance journalists in Indonesia and the strategies used to survive amid a pandemic that has not yet ended. This research uses a qualitative approach by observing the practice of journalism physically and in cyberspace and interviewing several key informants. The findings of this study show that internal company factors also adversely affect the condition of freelance journalists. Freelance journalists are often considered not an important part of the company, so some need to be equipped with standard equipment, adequate security equipment, and health insurance. So, to deal with this condition, some freelance journalists try to survive by applying individual tactics such as doing business on the sidelines of their journalistic activities. In addition, they also apply institutional strategies by strengthening networks through associations and professional communities.